INTERNALISASI NILAI SPORTIVITAS MELALUI PEMBELAJARAN PENDIDIKAN JASMANI DI SEKOLAH DASAR - Arifin, Syamsul (Sosio Religi: Jurnal Kajian Pendidikan Umum, 2017)
Primary School is a formal education level that foster students aged 7 to 12 years old, age enough sensitive to respond or imitate to stimulation from outside. Therefore, the proper internalization of sportsmanship values in elementary school provides a strong enough fundamentals of future student immorality, otherwise the errors in the methodological value internalization will also negatively impact the moral life of the individual in the future. This study aims to obtain an overview of the process of internalization of sportsmanship values through physical education in elementary education conducted at the State Primary School Loktabat 1 Banjarbaru. The subjects of this study are physical education teachers and students.